MACROZOOBENTHOS DIVERSITY AS A BIOINDICATOR OF WATER QUALITY IN THE CITUMANG RIVER, PANGANDARAN REGENCY, WEST JAVA - Despranta Tarigan, Ignatius
Citumang River is known as a body rafting tourist area, located approximately 13 km from Pangandaran Beach. The increase in tourism, domestic activities, and agriculture around the river can cause pollution that affects the composition of macrozoobenthos. This study aims to determine the water quality of the river based on the abundance and diversity of macrozoobenthos. Sampling was conducted in May and June 2024. Data analysis includes analysis of distribution, diversity, evenness and dominance of macrozoobenthos as well as statistical tests of the correlation between environmental parameters and abundance and diversity of macrozoobenthos. The results showed that there were 29 genus of macrozoobenthos found in the Citumang River. The highest abundance of macrozoobenthos was found at point S5 during low tide, followed by S5 during high tide, S4, S3, S2, and S1. The highest genus diversity was found at point S2, followed by S1, S5 during high and low tide, S4, and S3. Ischnura sp., Baetis sp., Ephemera sp., and Leptophlebia sp. serve as bioindicators at sampling points S1 and S2, indicating good water quality. Faunus sp. and Clibanarius sp. are bioindicators at points S4 and S5, indicating mildly polluted water influenced by tidal fluctuations. Clithon sp. and Melanoides sp. are bioindicators found at all sampling points, reflecting water quality ranging from good to mildly polluted, and also influenced by tidal fluctuations.